Photoelectron and fragmentation dynamics of the H++H+ dissociative channel in NH3 following direct single-photon double ionization - Larsen, Kirk A.; Rescigno, Thomas N.; Severt, Travis; Streeter, Zachary L.; Iskandar, Wael; Heck, Saijoscha; Gatton, Averell; Champenois, Elio G.; Strom, Richard; Jochim, Bethany; Reedy, Dylan; Call, Demitri; et al. (My University, 2020)
We report measurements on the H++H+ fragmentation channel following direct single-photon double ionization of neutral NH3 at 61.5 eV, where the two photoelectrons and two protons are measured in coincidence using three-dimensional (3D) momentum imaging. We identify four dication electronic states that contribute to H++H+ dissociation, based on our multireference configuration-interaction calculations of the dication potential energy surfaces. The extracted branching ratios between these four dication electronic states are presented. Of the four dication electronic states, three dissociate in a concerted process, while the fourth undergoes a sequential fragmentation mechanism. We find evidence that the neutral NH fragment or intermediate NH+ ion is markedly rovibrationally excited. We also identify differences in the relative emission angle between the two photoelectrons as a function of their energy sharing for the four different dication states, which bare some similarities to previous observations made on atomic targets.